Penerapan Algoritma Genetika Pada Pengenalan Paragraf - Erwin Saragih, Rejoice Iboy; Nababan, Darsono (Journal Information System Development (ISD), 2019)
Paragraph consists of sentences which has main idea. In this research, it applied the genetic algorithm to recognize a paragraph. It has several steps to do it, firstly on the alphabet forms word, then sentence, and finally paragraph. The process start from typing the paragraph and then the genetic algorithm will identify the paragraph accordingly by stages which are initial population, selection, crossover and mutation. Genetic algorithm is heuristic searching algorithm which based on nature selection of mechanism and nature genetics. Paragraph is a set of words or other characters with one or more languages are written especially if arranged in a customary order. The final result of this research is that showing the exact paragraph that is targeted.